Exposure dose measurement during diagnostic pediatric X-ray examination using an optically stimulated luminescence (OSL) dosimeter based on precise dose calibration taking into consideration variation of X-ray spectra. (December 2018) - Asahara, Takashi; Hayashi, Hiroaki; Goto, Sota; Tomita, Emi; Kimoto, Natsumi; Mihara, Yoshiki; Asakawa, Takumi; Kanazawa, Yuki; Katsumata, Akitoshi; Higashino, Kosaku; Yamashita, Kazuta; Okazaki, Tohru; et al.
Abstract: When dosimetry is performed in actual clinical situations using diagnostic X-rays, the energy dependence of the dosimeter should be taken into consideration. Although the dosimeter is calibrated with standard X-rays, it is unclear whether this dosimeter can be used in various clinical situations in which radiation exposure is not only caused by direct X-rays but also scattered X-rays. In this paper, in order to evaluate the applicability of an OSL dosimeter, we propose a novel method to derive a proper calibration factor using X-ray spectrum and the efficiency of the dosimeter. The X-ray spectra were calculated by means of a Monte-Carlo simulation code taking into consideration the effects of beam hardening, scattered X-rays and backscattering X-rays. As a result of analysis of calibration factors, we found that the difference of calibration factors from the standard, which was determined with 80 kV X-rays, was within 30%. Here, we focused our attention on dose measurement of medical staff who held a patient during pediatric X-ray examination; in this examination, a calibration factor can be determined precisely. In order to determine the dosimetric points, we mimicked a clinical situation using a neonate phantom and human dummies, and surface dose distributions to the human dummies were visualized. Based on the phantom study, we determined that the dosimetric positions of both hands and neck of the assistant during the actual clinical measurement were most important. Then, actual dosimetry in a clinical situation was performed. The OSL dosimeters were attached to the neck and hands of assistants during a pediatric X-ray examination, and doses were evaluated individually for each examination (N = 163). By analyzing data trends, we found that the dose to the assistant's hands was relatively higher when a younger patient was examined. In contrast, the dose to the neck position was the same regardless of the patient's age. In conclusion, we performed accurate dosimetry taking into consideration differences of X-ray spectra being incident to the dosimeter, and using our method, we can analyze individual doses to assistants for each pediatric X-ray examination. Highlights: A calibration method of an OSL dosimeter for medical dosimetry is proposed. We used simulated X-ray spectra and energy dependence of the dosimeter. Exposure doses to medical staff who hold pediatric patients were measured.